Komunikasi Inovasi Platform PaDi UMKM pada PT. Telkom Indonesia - Yogi Robiansyah; Asep Suryana; Meria Octavianti (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research explores the Pasar Digital Usaha Mikro, Kecil, dan Menengah (PaDi UMKM) platform, a notable B2B procurement platform that has attracted 127,000 MSMEs. Despite this, internal data indicates a significant participation gap. We applied a qualitative case study method, conducting interviews with employees and MSME actors, observing employee routines, and analyzing platform documentation. The study aimed to understand PaDi UMKM's innovation characteristics, development process, and communication strategies. Our findings categorize the platform as an innovative product, aligning with Rogers' innovation characteristics. Its development process is comprehensive, involving insight gathering, problem identification, research, idea generation, approval, testing, and launch. Innovation communication efforts were divided into five stages: knowledge, persuasion, decision, implementation, and confirmation. These were executed through various channels like social media content, brand activation programs, external collaborations, and MSME educational mentoring to foster sustainable adoption. Key barriers to long-term adoption identified were low digital literacy, platform bugs or errors, and administrative incompleteness. The study emphasizes the critical need for active involvement from diverse stakeholders to ensure the platform's sustained success.